KARAKTERISTIK TOP MANAGEMENT DAN KUALITAS AUDIT EKSTERNAL SEBAGAI VARIABEL MODERASI DALAM MENDUKUNG CORPORATE SUSTAINABILITY PERFORMANCE - Cahya Maharani, (2023)
This research is a quantitative study that aims to examine the influence of TMT size and CEO's education on the company's sustainability performance in terms of each aspect such as economic, environment, and social. The data used in this study is secondary data using annual reports and sustainability reports. The samples used in this study are 177 non financial companies that are listed in the Indonesian Stock Exchange (IDX) during the period of 2019-2021. Multiple linear regression and panel data regression were used as the analysis techniques using STATA 14. The results of this study show that (1) TMT size does not have a significant effect towards economic sustainability performance (2) TMT size does not have a significant effect towards environment sustainability performance (3) TMT size does not have a significant effect towards social sustainability performance (4) CEO education does not have a significant effect towards economic sustainability performance (5) CEO education does not have a significant effect towards environment sustainability performance (6) CEO education does not have a significant effect towards social sustainability performance (7) external audit quality is not able to moderate the relationship between TMT size and economic, environment, social sustainability performance (8) external audit quality is not able to moderate the relationship between CEO education and economic, environment sustainability performance (9) external audit quality is able to moderate the relationship between CEO education and social sustainability performance